TAIWAN STRATEGY AND DIPLOMACY RESPONSE TO ONE-CHINA POLICYDURING MA YING JEOU ADMINISTRATION 2008- 2015 - Baiq Syahrika Rahayu (HI 16 UMY 110, 2016)
*110 After the lost from the communist and after the expulsion from UN membership Taiwan face a hard time in gaining recognition from international community. The fact that China has risen as a new super power also quite a threat for Taiwan as China would have tighten its grip toward Taiwan international space. Taiwan, on the other hand, has put a concern toward this issue. Ma Ying-Jeou one of the leaders of Taiwan also not forget to put much concern in this issue. This paper would analyze about the strategy and diplomacy Taiwan use in response to the one china policy. The analysis would began with realist theory saying that â€œthe world in state of anarchy and that power is important yet state is rational so it will select strategy that will minimize it lost and maximize the benefitâ€. Hence it goes the same to Taiwan nowadays condition under the One-China Policy. It will select strategy that will most benefit Taiwan. Looking to the fact Taiwan compare to China is lost in term of hard power possession so it would most likely that seeking for alliance and choosing Public diplomacy as the means on utilizing the soft power at it best.